Feline Accommodation: Balancing Pet Hotel Business Models in Russia: Akomodasi Kucing: Menyeimbangkan Model Bisnis Hotel Hewan Peliharaan di Rusia - Ahmadbekova Kimyo; Sobirov Bobur (Academia Open, 2023)
This research paper investigates the establishment of pet hotels as a viable business venture, with a specific focus on the Russian market. Through an analysis of various business models in the pet hotel industry, the study aims to identify areas for improvement and propose strategies for enhancing the overall efficiency and success of such enterprises. Utilizing a combination of qualitative and quantitative methods, the research evaluates the strengths and weaknesses of existing pet hotel models in Russia, considering factors such as pricing, service offerings, and customer satisfaction. The findings of this study contribute to a comprehensive understanding of the business landscape in the pet hotel industry and provide insights for entrepreneurs seeking to establish or optimize their pet hotel operations. Ultimately, the research culminates in the development of a well-balanced business model tailored specifically for cat accommodation, offering a compelling solution for entrepreneurs in the global pet hotel domain. Highlights: The research examines various business models in the pet hotel industry in Russia, focusing on feline accommodation. The study identifies areas for improvement within existing pet hotel models and proposes strategies for enhancing their efficiency and success. The research results in the development of a well-balanced business model specifically tailored for cat accommodation, offering valuable insights for entrepreneurs in the global pet hotel domain. Keywords: Pet hotels, business models, Russia, feline accommodation, improvement.